Diary of a Dismissed Delegate : Public Good at the Mercy of Bureaucracy and Sycophancy in Cameroon. - Ngwane, George, 1960- (Langaa RPCIG, 2016)
Diary of a Dismissed Delegate is the personal story of the trials and travails of George Ngwane as a civil servant in Cameroon. With documented evidence in support, the book delves into the destructive machinations of the bureaucracy and sycophancy at the heart of the Cameroonian public service, and its detrimental effects on meritocracy and the public good. It is a system where the personalisation of power devalues virtue, devotion and dedication to truth and the call of justice. For a country that has the ambition to recapture her lost middle income status, one that boasts of a huge critical mass of human capital, and that has all the potentials of a double digit economic development, political patronage and intolerance to creative freedom must be anathema.